STUDI SIMULASI : PERBANDINGAN UJI WELCH DAN UJI COHRAN COX PADA MASALAH BEHRENS-FISHER - Sudartianto Sudartianto; Yudhi Andriyana; Riaman Riaman (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2017)
Behrens-Fisher problem has a lot of test, two of them are Cohran-Cox test and Welch test. This study will examine the stability of both tests by comparing thesignificance levels of both tests to a specific (given) significance level. The result shows that the Welch test is more stable than the Cochran-Cox test which means that theoretically Welch test is better than Cochran-Cox test.